Improving uptake of flexible sigmoidoscopy screening: a randomized trial of nonparticipant reminders in the English Screening Programme - Kerrison, Robert S.; McGregor, Lesley M.; Marshall, Sarah; Isitt, John; Counsell, Nicholas; Rees, Colin J.; von Wagner, Christian (Endoscopy, 2017)
Background and study aims Uptake of flexible sigmoidoscopy screening in the English Bowel Scope Screening (BSS) Programme is low. The aim of this study was to test the impact of a nonparticipant reminder and theory-based leaflet to promote uptake among former nonresponders (previously did not confirm their appointment) and nonattenders (previously confirmed their appointment but did not attend).Patients and methods Eligible adults were men and women in London who had not attended a BSS appointment within 12 months of their invitation. Individuals were randomized (1:1:1) to receive no reminder (control), a 12-month reminder plus standard information booklet (TMR-SIB), or a 12-month reminder plus bespoke theory-based leaflet (TMR-TBL) designed to address barriers to screening. The primary outcome of the study was the proportion of individuals screened within each group 12 weeks after the delivery of the reminder.Results A total of 1383 men and women were randomized and analyzed as allocated (n = 461 per trial arm). Uptake was 0.2 % (n = 1), 10.4 % (n = 48), and 15.2 % (n = 70) in the control, TMR-SIB, and TMR-TBL groups, respectively. Individuals in the TMR-SIB and TMR-TBL groups were significantly more likely to attend screening than individuals in the control group (adjusted odds ratio [OR] 53.7, 95 % confidence interval [CI] 7.4 – 391.4, P < 0.001 and OR 89.0, 95 %CIs 12.3 – 645.4, P < 0.01, respectively). Individuals in the TMR-TBL group were also significantly more likely to attend screening than individuals in the TMR-SIB group (OR 1.7, 95 %CIs 1.1 – 2.5, P = 0.01). Across all groups, former nonattenders were more likely to participate in screening than former nonresponders (uptake was 14.2 % and 8.0 %, respectively; OR 2.5, 95 %CIs 1.4 – 4.4, P < 0.01). The adenoma detection rate among screened adults was 7.6 %, which is comparable to the rate in initial attenders.Conclusions Reminders targeting former nonparticipants can improve uptake and are effective for both former nonresponders and nonattenders. Theory-based information designed to target barriers to screening added significantly to this strategy.